2020
DOI: 10.14716/ijtech.v11i1.2464
|View full text |Cite
|
Sign up to set email alerts
|

Performance Factors for Successful Business Incubators in Indonesian Public Universities

Abstract: Measuring the performance of business processes is already a main concern for both faculty and enterprise players, since organizations are motivated to reach the productivity stage. Employing a performance achievement framework for the relationship between business incubator success factors will guarantee connection with commercial schemes, which support a high level of performance indicators in successful business incubator models. This research employs a quantitative approach, with the data analyzed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…Although peer-to-peer lending services have a variety of risks in their use, several studies have shown an increase in the interest of companies, markets, and the public in using these services (Magee, 2011;Frame and White, 2014;Xie et al, 2016;Prayogo, 2017;Gozali et al, 2020). The number of fintech service providers continues to increase, and some of the results of previous studies conclude that consumer acceptance is a major determinant of the development of fintech in a country (Agarwal et al, 2009;Ben Mansour, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although peer-to-peer lending services have a variety of risks in their use, several studies have shown an increase in the interest of companies, markets, and the public in using these services (Magee, 2011;Frame and White, 2014;Xie et al, 2016;Prayogo, 2017;Gozali et al, 2020). The number of fintech service providers continues to increase, and some of the results of previous studies conclude that consumer acceptance is a major determinant of the development of fintech in a country (Agarwal et al, 2009;Ben Mansour, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Performance variables are used as dependent variables in regression models. Many different indexes are used to measure performance (Gozali et al, 2020). In one type of research the authors use absolute performance indicators such as gross profit, revenue, and net profit (Santos and Brito, 2009;Fried and Tauer, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Educational institutions are regarded as part of social infrastructure [ 67 ]. Prior research also revealed that technology startups are more likely to develop a link with educational institutions [ 68 – 72 ], while other research has shown that the interaction between incubated firms and local universities is limited, and not always successful [ 73 77 ]. Thus, we developed another hypothesis to examine whether the presence of universities affects the performance of incubators:…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%